GENDER-BASED CYBER VIOLENCE IN CIREBON REGENCY: A CRITICAL GENDER AND LEGAL ANALYSIS - Leliya Leliya; Muhamad Mujahidin; Muhamad Dadan Wildanuddin (UIN Siber Syekh Nurjati Cirebon, 2025)
The rapid expansion of digital technology and social media has facilitated the emergence of Gender-Based Cyber Violence (GBCV). In Cirebon Regency, reported cases increased sharply from three in 2023 to eight in 2024, reflecting a 166 percent rise and highlighting the growing risks faced by women in digital environments. This study aims to comprehensively examine GBCV in Cirebon Regency by integrating gender analysis, feminist legal theory, positive law, and Islamic law to evaluate existing legal protections and formulate a more responsive and victim-centered protection framework. This research employs a qualitative descriptive approach using primary data from victims of GBCV, local government officials, NGO, and experts in Islamic and positive law, complemented by secondary data derived from relevant legal regulations. Data were collected through interviews, document analysis, FGD, and questionnaires to support a comprehensive qualitative analysis. The results show that from 2020 to 2025 the dominant forms of GBCV in Cirebon Regency were sexting (6 cases), cyber grooming (5 cases), and impersonation (5 cases). Contributing factors include low digital literacy, patriarchal norms, victim blaming, and the absence of a dedicated cybercrime unit within the Cirebon Police Resort. The legal analysis reveals that the implementation of the Electronic Information and Transactions Law, the Sexual Violence Crime Law, and regional regulations remains insufficiently gender responsive, while the principles of maqaṣid shariah affirm that GBCV violates the protection of human dignity, honor, and life. This study contributes a gender informed and Islamic values-based integrative framework to enhance policies for protecting women in digital environments.